Investigating Critical Thinking Skills in Rural Middle School Students through STEM Education: A Qualitative Case Study from Sumedang - hajar, maya umi; Nurmalasari, Santy; Darmawan, Akhmad (SEAMEO QITEP in Science, 2025)
Learning plays a crucial role in fostering students’ critical thinking skills, enabling them to address the challenges they face in their daily lives. This study was conducted in Sumedang, West Java, where students experience limited water availability. The main water sources are located far from residential areas, requiring students to make long trips each morning to fetch water from a distant river. This qualitative descriptive study aimed to explore how students employ critical thinking skills while engaging in contextual STEM learning through the development of a non-electric water pump project. The project involved seventh-grade students participating in science classes using a contextual STEM approach over one semester. Data were collected and analysed through observation, document analysis, and audio and video recordings using Transcript-Based Lesson Analysis. Indicators of critical thinking such as questioning, articulating assumptions, and demonstrating open-mindedness were observed during the STEM learning process of designing the non-electric water pump. The emergence of these skills varied across learning phases, individual characteristics, and group dynamics. Contextual STEM learning not only promotes critical thinking but also equips students with essential life skills for global competition in the 21st century by preparing them to solve real-world problems. The findings of this study provide insights for educators in designing more meaningful science learning experiences in the future.